2017
DOI: 10.1111/and.12846
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metformin on germ cell-specific apoptosis, oxidative stress and epididymal sperm quality after testicular torsion/detorsion in rats

Abstract: The study was designed to evaluate the effects of metformin on apoptosis and epididymal sperm quality in a rat testicular ischaemia/reperfusion (I/R) injury model. A total of 72 male rats were divided into four groups (n = 18 for each group): group 1 (sham-operated group), group 2 (metformin group), group 3 (torsion/detorsion [T/D] + saline) and group 4 (T/D + 300 mg kg metformin). Testicular torsion was achieved by rotating the right testis 720° in a clockwise direction for 1 hr. Tissue malondialdehyde (MDA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 60 publications
4
22
0
Order By: Relevance
“…Deemeh et al [38] revealed that male partners of couples with RPL had high levels of protamine deficiency. As DNA integrity plays a key role in sperm function, it can be a better predictor of sperm fertility potential than conventional sperm parameters [39]. The results of three studies conducted by Aoki et al showed that more severe protamine deficiency was related to DNA damage in infertile men [11,14,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deemeh et al [38] revealed that male partners of couples with RPL had high levels of protamine deficiency. As DNA integrity plays a key role in sperm function, it can be a better predictor of sperm fertility potential than conventional sperm parameters [39]. The results of three studies conducted by Aoki et al showed that more severe protamine deficiency was related to DNA damage in infertile men [11,14,40].…”
Section: Discussionmentioning
confidence: 99%
“…The results of three studies conducted by Aoki et al showed that more severe protamine deficiency was related to DNA damage in infertile men [11,14,40]. Previous research demonstrated a positive correlation between reactive oxygen species levels and apoptosis rate in seminal plasma [39,41]. Antioxidants have been observed to reduce apoptosis in testicular cells and to improve sperm quality [42].…”
Section: Discussionmentioning
confidence: 99%
“…For example, metformin and clomifene are currently being prescribed for females for the management of polycystic ovarian syndrome (PCOS), with positive results (Palomba et al ., ). Also, experimental studies have found metformin beneficial in protecting the hippocampus (Ge et al ., ), heart (Apaijai et al ., ), and testis (Asghari et al ., ; Ghasemnejad‐Berenji et al ., ) from ischemia–reperfusion injury. It also increases androgen and estrogen receptor expressions in the testis and increases serum testosterone level in diabetic rats (Nasrolahi et al ., ; Ayuob et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…By means of this mechanism, Al reduces pituitary gonadotropin release, causing a decrease in the sperm count (Cheraghi, Golkar, Roshanaei, & Alani, ). Oxidative damage causes injuries in the testicular tissue and reduces the germ cells (Ghasemnejad‐Berenji et al, ). Reactive oxygen compounds (ROS), emerging due to the oxidative damage, play a central role in a series of pathological conditions in association with the environmental factors including inflammation, toxicity and endocrine disorders.…”
Section: Introductionmentioning
confidence: 99%